Preliminary phytochemical analysis & Invitro Antibacterial activity of Acacia catechu willd Bark against Streptococcus mitis, Streptococcus sanguis & Lactobacillus acidophilus. - Lakshmi T,; Aravind kumar S, (International Journal of Phytomedicine, 2011)
The objective of our study is to investigate the in vitro antibacterial activity of ethanolic bark extract of Acacia catechu willd against selected oral microbes and to investigate the phytochemicals present in it. The inhibitory effect of the extract were tested against selected oral microbes by using the Macro broth dilution method .The ethanolic bark extract of Acacia catechu exhibited antibacterial activity against streptococcus mitis with minimum bactericidal concentration of 500µg/ml whereas the MBC for streptococcus sanguis and Lactobacillus acidophilus were found to be 1mg/ml, 5mg/ml,10mg/ml and the phytochemical analysis revealed the presence of tannins, flavonoids, amino acids , saponins, triterpenoids. The ethanolic bark extract of Acacia catechu willd was found to be bactericidal in action against tested bacterial strains and these action may be due to the presence of phytochemical constituents in it.